Differences in running biomechanics between young, healthy men and women carrying external loads - Rubio, Jose E.; Tong, Junfei; Sundaramurthy, Aravind; Subramani, Adhitya V.; Kote, Vivek Bhaskar; Baggaley, Michael; Edwards, W. Brent; Reifman, Jaques (Frontiers in Bioengineering and Biotechnology, 2023)
During U.S. Army basic combat training (BCT), women are more prone to lower-extremity musculoskeletal injuries, including stress fracture (SF) of the tibia, with injury rates two to four times higher than those in men. There is evidence to suggest that the different injury rates are, in part, due to sex-specific differences in running biomechanics, including lower-extremity joint kinematics and kinetics, which are not fully understood, particularly when running with external load. To address this knowledge gap, we collected computed tomography images and motion-capture data from 41 young, healthy adults (20 women and 21 men) running on an instrumented treadmill at 3.0 m/s with loads of 0.0 kg, 11.3 kg, or 22.7 kg. Using individualized computational models, we quantified the running biomechanics and estimated tibial SF risk over 10 weeks of BCT, for each load condition. Across all load conditions, compared to men, women had a significantly smaller flexion angle at the trunk (16.9% to 24.6%) but larger flexion angles at the ankle (14.0% to 14.7%). Under load-carriage conditions, women had a larger flexion angle at the hip (17.7% to 23.5%). In addition, women had a significantly smaller hip extension moment (11.8% to 20.0%) and ankle plantarflexion moment (10.2% to 14.3%), but larger joint reaction forces (JRFs) at the hip (16.1% to 22.0%), knee (9.1% to 14.2%), and ankle (8.2% to 12.9%). Consequently, we found that women had a greater increase in tibial strain and SF risk than men as load increases, indicating higher susceptibility to injuries. When load carriage increased from 0.0 kg to 22.7 kg, SF risk increased by about 250% in women but only 133% in men. These results provide quantitative evidence to support the Army’s new training and testing doctrine, as it shifts to a more personalized approach that shall account for sex and individual differences.